Damage Mechanics and Micromechanics of Localized Fracture Phenomena in Inelastic Solids - Voyiadjis, George Z. (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2011)
This book resulted from a series of lecture notes presented in CISM, Udine in July 7 -11, 2008. The papers inform about recent advances in continuum damage mechanics for both metals and metal matrix composites as well as the micromechanics of localization in inelastic solids. Also many of the different constitutive damage models that have recently appeared in the literature and the different approaches to this topic are presented, making them easily accessible to researchers and graduate students in civil engineering, mechanical engineering, engineering mechanics, aerospace engineering, and material science.